THE APPLICATION OF GENERATIVE AI IN EDUCATIONAL RESEARCH: A SYSTEMATIC LITERATURE REVIEW - Techasermwattanakul, Pongsakorn; Suwannatthachote, Praweenya (Journal of Education and Innovation, 2025)
This study is a systematic literature review with the aim of studying the use of Generative AI in educational research and presenting guidelines for applying AI in the teaching and learning process. The systematic literature review selected 18 articles from foreign research related to the use of Generative AI during 2021-2023. The results show that AI is used in three main ways: supporting learning, creating and improving learning media, and assessing and tracking learning to provide feedback. For example, ChatGPT and ChatBot are used as teaching assistants. Platforms such as Midjourney and Synthesia are used to create interactive learning media. ChatGPT is also used to assess and provide specific feedback to students. The use of AI in education has shown potential to improve learning and teaching experiences. However, there are still challenges in terms of access and equity in education. Therefore, the use of AI should be considered in terms of design that takes into account social factors and access to technology. This is to create more inclusive and equitable education.